2017
DOI: 10.1007/s12223-017-0569-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical strains of Lactobacillus reduce the filamentation of Candida albicans and protect Galleria mellonella against experimental candidiasis

Abstract: Candida albicans is the most common human fungal pathogen and can grow as yeast or filaments, depending on the environmental conditions. The filamentous form is of particular interest because it can play a direct role in adherence and pathogenicity. Therefore, the purpose of this study was to evaluate the effects of three clinical strains of Lactobacillus on C. albicans filamentation as well as their probiotic potential in pathogen-host interactions via an experimental candidiasis model study in Galleria mello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…Apart from traditional antifungal compounds, there is also a growing interest in the use of probiotic bacteria as agents against C. albicans . In a recent study, the antifungal activity of clinical isolates of Lactobacillus strains were tested against C. albicans biofilms in vitro and it was shown that certain species of lactobacilli had an effect on C. albicans morphogenesis and biofilm formation 317 318 . Using the G. mellonella model system the same group showed that these probiotic bacteria reduce filamentation by C. albicans and also stimulate the host innate immune system, thereby protecting the host against C. albicans infections 319 .…”
Section: Methods For Monitoring In Vivo Performancmentioning
confidence: 99%
“…Apart from traditional antifungal compounds, there is also a growing interest in the use of probiotic bacteria as agents against C. albicans . In a recent study, the antifungal activity of clinical isolates of Lactobacillus strains were tested against C. albicans biofilms in vitro and it was shown that certain species of lactobacilli had an effect on C. albicans morphogenesis and biofilm formation 317 318 . Using the G. mellonella model system the same group showed that these probiotic bacteria reduce filamentation by C. albicans and also stimulate the host innate immune system, thereby protecting the host against C. albicans infections 319 .…”
Section: Methods For Monitoring In Vivo Performancmentioning
confidence: 99%
“…Besides, the number of anaerobic bacteria and abundance of Lactobacillus were all significantly reduced in ABX mice. However, a decrease in anaerobic bacteria could promote overgrowth of Candida glabrata [73], Lactobacillus crispatus could modulate epithelial cell defense against C. albicans [65], clinical strains of Lactobacillus could influence the growth and expression of C. albicans virulence factors [58], and the metabolites of L. gasseri and L. crispatus could downregulate biofilm formationrelated genes of C. albicans, thus inhibiting biofilm formation of C. albicans [59]. These previous studies suggest that we should explore in detail the specific mechanisms by which members of the intestinal microbiota communicate with the host immune system and identify specific species as different members of intestinal microbiota elicit different immune responses relating to itself or its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae abundance was decreased in a model of ulcerative colitis [57]. Lactobacillus could reduce the virulence of C. albicans [58], and its metabolites inhibit C. albicans biofilm formation [59]. In summary, there were significant changes in intestinal microbiota structure between ABX and CNV mice, and the significant discrepant bacteria may play a key role during invasive candidiasis in mice and further study is required to explore the specific bacteria which actually work during invasive candidiasis.…”
Section: Overall Intestinal Microbiota Structure Was Changed In Abx Micementioning
confidence: 99%
“…Various members of the human microbiota have been shown to produce inhibitors of 344 C. albicans hypha formation or virulence 13,14,16 . Often the actual inhibitory molecule is not 345 known and constitutively produced [41][42][43] . These observations suggest that bacteria inhabiting 346 the gastrointestinal tract along with C. albicans may utilize an inhibitory strategy to enhance 347 their ability to co-exist with C. albicans in their common niche.…”
Section: Damage 318mentioning
confidence: 99%